2003
DOI: 10.1097/01.tp.0000062662.63663.e8
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural integrity of porcine pancreatic grafts subjected to a period of warm ischemia and cold preservation with histidine-tryptophan-ketoglutarate (custodiol) or University of Wisconsin solution

Abstract: Porcine pancreatic grafts are viable after 16-hr CI following 15-min WI in this experimental nonheartbeating donor model. HTK solution seems to provide reliable graft function in this setting and to be equivalent to UW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
(28 reference statements)
1
14
0
1
Order By: Relevance
“…Furthermore, A closer examination of the allograft survival curves in Figure 2 suggested a dominant early effect of preservation solution; this was consistent with a recent single-center report (2). To differentiate between early and late effects in the national population, we developed a multivariate Reduced Pancreas Graft Survival with HTK these results are the short CIT (<12 h) in this (4) and prior case series (2,(5)(6)(7)(8)(9) (13)(14)(15)(16)(17). These gross findings also correlated with histological evidence of increased interstitial edema and cellular swelling (15)(16)(17).…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, A closer examination of the allograft survival curves in Figure 2 suggested a dominant early effect of preservation solution; this was consistent with a recent single-center report (2). To differentiate between early and late effects in the national population, we developed a multivariate Reduced Pancreas Graft Survival with HTK these results are the short CIT (<12 h) in this (4) and prior case series (2,(5)(6)(7)(8)(9) (13)(14)(15)(16)(17). These gross findings also correlated with histological evidence of increased interstitial edema and cellular swelling (15)(16)(17).…”
Section: Methodssupporting
confidence: 54%
“…To differentiate between early and late effects in the national population, we developed a multivariate Reduced Pancreas Graft Survival with HTK these results are the short CIT (<12 h) in this (4) and prior case series (2,(5)(6)(7)(8)(9) (13)(14)(15)(16)(17). These gross findings also correlated with histological evidence of increased interstitial edema and cellular swelling (15)(16)(17). At least one group noted clinical correlation with HTKpreserved human pancreas allografts, as they reported that all HTK-flushed pancreas allografts appeared more edematous as compared to UW-flushed pancreas allografts (7).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a porcine model of DCD, using 15‐min warm ischemia followed by 16 h of cold ischemia has shown HTK to be as effective as UW for pancreas preservation. There was less biochemical evidence of pancreatitis within the grafts and similar values of intravenous glucose tolerance testing amongst autografted recipients (146).…”
Section: Static Cold Pancreas Preservation For Pancreas Transplantationmentioning
confidence: 97%
“…This solution has a low viscosity, easy handling properties, and a relatively low cost. Some studies have demonstrated similar results between UW and HTK solutions for pancreas preservation, in not only experimental animal models [43, 50, 51] but also clinical pancreas transplantation [5254]. We used HTK solution with ulinastatin (modified HTK solution (M-HTK)) in this study because MK solution includes ulinastatin.…”
Section: Preservation Solutionmentioning
confidence: 99%